Witnessing distress : Cultural workers’ processing of pandemic experiences on social media platforms - Soronen, Anne (United States, 2025)
This article examines the ways in which Finnish cultural workers experienced and responded to their colleagues’ and peers’ distress on social media platforms during the prolonged COVID-19 pandemic. The theory of media witnessing as mundane world-witnessing is employed to analyse cultural workers’ modalities of experience as audience-like followers on social media. The data comprise 26 focused interviews conducted via Zoom and over phone in 2021 with cultural workers representing the fields of theatre, television and film industry, literature, music and circus. We argue that various modes of affective and politicised witnessing offered cultural workers the mechanisms to articulate and reflect on their own and others’ experiences of inequality and vulnerability as well as develop a sense of responsibility. In the context of the pandemic, mundane world-witnessing involved engagement and identification with distress, peer support and activism, as witnessed and evaluated by cultural workers on social media. Furthermore, this article theorises a new mode of witnessing prevalent on social media platforms – speculative witnessing – which carries a reflective and hesitant approach to social media ‘bubbles’, obscure algorithmic agency and imagination of absent audiences. In other words, speculative witnessing captures a dimension of metacommunicative scepticism in media witnessing that reflects a specific condition of knowing in the context of social media platforms.